2019
DOI: 10.1186/s40608-019-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with overweight and obesity among adults in Hawassa city, southern Ethiopia: a community based cross-sectional study

Abstract: Background In Ethiopia, limited information is available about the epidemiology of over-nutrition. This study assessed the prevalence of, and factors associated with overweight and obesity among adults in Hawassa city, Southern Ethiopia. Methods A community-based cross-sectional survey was conducted in August 2015 in the city. A total of 531 adults 18–64 years of age were selected using multistage sampling approach. Interviewer administered qualitative food frequency qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
75
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 28 publications
19
75
2
2
Order By: Relevance
“…The adverse health consequences of overweight and obesity are well described in the general population and in HIV/AIDS patients. 23 In this study, we examined patients at HIV follow-up clinic in Jimma zone hospitals, Ethiopia, and found that the magnitude of overweight and obesity were 21%. It was found that older age, female sex, early stage of the disease, lower CD4 count and absence of mild to moderate physical activity were significant predictor of obesity/overweight.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse health consequences of overweight and obesity are well described in the general population and in HIV/AIDS patients. 23 In this study, we examined patients at HIV follow-up clinic in Jimma zone hospitals, Ethiopia, and found that the magnitude of overweight and obesity were 21%. It was found that older age, female sex, early stage of the disease, lower CD4 count and absence of mild to moderate physical activity were significant predictor of obesity/overweight.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse health consequences of overweight and obesity are well described in the general population and in HIV/AIDS patients (24) In this study, we examined patients at HIV follow up clinic in JUSTH, Ethiopia, and found that overweight and obesity were highly prevalent, although not as high as that found in the general population. It was found that older age , female sex , early stage of the disease, lower CD4 cunt and absence of mild to moderate physical activity were significant predictor of obesity/overweight.…”
Section: Resultsmentioning
confidence: 90%
“…6,25,49 Unlike other studies, we found in this study, women with a higher proportion of T2DM compared to men. This discrepancy could be due to a higher rate of obesity among women compared to their men counterparts 29,30 and history of gestational diabetes mellitus, which is associated with increased risk of subsequent T2D in mothers. 11,28 It is imperative to acknowledge, as our results must be viewed in light of several important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Studies in the US, Italy, and Ethiopia indicate that male participants had a higher risk than female study participants in all age-groups for both type 1 and type 2 diabetes. 17,19,20 But other studies in SSA countries suggested that the prevalence of diabetes is higher among women compared to men; this is due to higher rates of obesity among women, 29,30 or history of gestational diabetes mellitus, which is associated with an increased risk of subsequent T2D in mothers and their offspring. 11,28 Although diabetes brings real economic loss by increased use of health services, loss of productivity, disability and premature death in the developing nations including Ethiopia, robust data on adult diabetes are scarce in Ethiopia as well in Tigray; where most clinical data are not timely assessed and made accessible for policy and decision-makers.…”
Section: Introductionmentioning
confidence: 98%